COMMON LAW VS. CIVIL LAW: WHICH SYSTEM PROVIDES MORE PROTECTION TO SHAREHOLDERS AND PROMOTES FINANCIAL DEVELOPMENT - SARKAR, Prabirjit (Journal of Advanced Research in Law and Economics, 2017)
This study re–examines the theory of legal–origin on the basis of a new longitudinal dataset for four OECD countries (UK, USA, France and Germany) over a long time span 1970–2005. It observes that the civil law countries (France and Germany) provided better minority shareholder protection. Through dynamic panel data modelling our study shows that minority shareholder protection has a long–term favourable effect only on stock market listing of firms. Thus, our study questions the proposition that common–law countries provide more protection to their shareholders; it also casts doubt on the related proposition that shareholder protection promotes stock market development.